Selected Papers from XVI MaNaPro and XI ECMNP - Vasconcelos, Vítor; Gaudencio, Susana P; Pedrosa, Rui (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The oceans harbor the majority of the Earth´s biodiversity. Marine organisms/microorganisms provide a diverse array of natural products, which are important sources of biologically active agents with unique chemical structures and a broad range of medical and biotechnological applications. The XVI MaNaPro and XI ECMNP conferences aim to present advances and future perspectives on marine natural product research to the scientific community by gathering scientists who work in marine chemistry and related scientific fields from all over the world and at different seniority levels. This Special Issue was organized on the occasion of the 2nd joint XVI MaNaPro and XI ECMNP meeting (http://wmnp2019.ipleiria.pt/) held in Peniche, Portugal, in 2019. It comprises 12 original research articles that exemplify research performed in the scope of the conference topics